PERANCANGAN DAN PENERAPAN SISTEM PENDUKUNG KEPUTUSAN UNTUK KENAIKAN JABATAN ( KARYAWAN KONTRAK MENJADI KARYAWAN TETAP ) DENGAN MENGGUNAKAN METODE SIMPLE ADDITVE WEIGHTING (SAW) PADA PT. PRINTEC PERKASA II - Abdul Halim Ansor; Irpan Apandi2 (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Printec Perkasa II is a company engaged in printing and packaging. Employees are very important resources to determine the success of a work unit. efforts to improve the quality of the performance of an employee, namely the promotion of contract employees to permanent employees. Promotion is an award given for work performance and employee loyalty to the company. Decision Support System (SPK) which can help make it easier to determine an employee can be said to be eligible for promotion. In this study the decision-making calculation method used is Simple Additive Weighting (SAW) with 4 criteria, namely Discipline, Job Performance, Psychotest and Interview. The system was built using the PHP programming language. The test results using the Black Box Test indicate that the system can function according to user needs and the system is declared to have met the criteria for promotion of contract employees to contract employees at PT. Printec Perkasa II. Keywords : Decision support system, contract employees become permanent employees, PHP, Simple Additve Weigthing (SAW)